Mandela : The Life of Nelson Mandela - Green, Rod (New York Thomas Dunne Books, St. Martin's Press, 2012)
The life of Nelson Mandela, one of the most charistmatic statesmen of all time, is celebrated in this book with a unique collection of photographs telling the story of his rise from humble beginnings in the tribal huts of his native Transkei to become a firebrand lawyer, political campaigner, Nobel Prize winner and President of South Africa.
Keywords: Mandela, Nelson -- 1918-2013; African National Congress; Political prisoners -- Biography -- South Africa